Fairness in Round-Robin Tournaments with Four Players and Endogenous Sequences - Fabian Dietz; Marco Sahm (CESifo GmbH, 2024)
We examine the effects of endogenous sequences on the fairness in round-robin tournaments with four players, multiple prizes, and general contest technologies. A tournament is called horizontally ex-ante fair if symmetric contestants have the same expected payoffs (odds) before the tournament starts. It is called perfectly fair if the winning probabilities in each match depend only on the players' characteristics but not on the position of the match in the course of the tournament. We show that there is no sequence which implies perfect fairness. By contrast, some endogenous sequences imply horizontal ex-ante fairness irrespective of the prize structure. In winner-take-all tournaments, additional endogenous sequences are horizontally ex-ante fair. Our findings question the prevailing use of exogenous sequences in four-player round-robin tournaments in commercial sports despite horizontally ex-ante fair alternatives.
Keywords: C72; D72; Z20; 330; sequential round-robin tournament; endogenous sequence; contest success function; multiple prizes; fairness